Mental Health Service Program (SEJIWA): Policy Innovation for Family Resilience as Social Recovery during the Covid-19 Pandemic - Annora Febrila Nilamsari; Adettia Gama; Lili Hasmi (Jurnal Manajemen Pelayanan Publik, 2023)
The impact of the Covid-19 pandemic is multidimensional. It was not only limited to health sectors, but also to socio-cultural sectors. The Covid-19 Pandemic crisis has increased mental health risks for people of all ages, including children and parents in Indonesia. In an effort to overcome this, the central government of the Republic of Indonesia has released the Mental Health Service Program (SEJIWA) which has received enthusiasm from the community. This research uses qualitative research methods with a literature study approach and Actor Network Theory (ANT) on SEJIWA Services and the concept of Mental Health Policy. The purpose of this research is to develop an innovative SEJIWA Family Care Program which aims to assist families in carrying out their roles and functions and establish appropriate regularity in daily activities. The results of this study indicate that the SEJIWA Family Care Program in the Actor Network-Theory (ANT) review shows that innovation in strengthening family resilience in Indonesia has shown a collective movement of many actors involved, but these efforts need to continue to be strengthened through evaluation and improvement of services that increasingly focus on the governmental policy to relationships and emotions in the family as the most micro sphere of development in the framework of social recovery efforts in the post-Covid-19 pandemic in Indonesia.